A critical review on the evolution and development of inland port research. (January 2019) - Witte, Patrick; Wiegmans, Bart; Ng, Adolf K.Y.
Abstract: Over the past twenty-five years a considerable amount of literature has emerged that addresses inland port development in a variety of ways and in different institutional contexts. A recurring issue throughout most papers focusing on inland ports is the wide diversity of definitions, actors, functions, levels and geographies that are of relevance. Therefore, a literature review on inland port development contributes to defining the most important streams in inland port research. Recent studies show that the concept of inland ports is clearly much richer and more diversified than merely an extension of deep-sea ports or port logistics. However, as much of the literature is still largely based on individual case studies and anecdotal evidences, the conceptualization of inland ports has proven to be particularly difficult. Therefore, this review paper presents a systematic and integrated review of inland port studies, covering 80 international peer-reviewed academic journal papers on inland port development between 1992 and 2017. The results show that much attention is paid on inland ports as components of the 'transport/logistics/supply chain' systems (follower), while their roles as components of the 'regional' systems (leader) are largely overlooked. Such a tweaked focus is likely to pose significant impacts on planning, management, and governance of inland ports.